Solid electrolyte and electrode mixture using the same, solid electrolyte layer, solid-state battery

By introducing lithium halide of a specific structure into the solid electrolyte of a solid state battery and controlling its microcrystal size, the problem of hydrogen sulfide production in the sulfide solid electrolyte is solved, and the effect of high lithium ion conductivity and low hydrogen sulfide production is achieved.

CN114556492BActive Publication Date: 2025-03-21MITSUI MINING & SMELTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080072323.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-29
Filing Date
2020-10-20
Publication Date
2025-03-21
Estimated Expiration
2040-10-20

AI Technical Summary

Technical Problem

The sulfide solid electrolyte in existing solid-state batteries is prone to react with moisture in the atmosphere to produce hydrogen sulfide, and lithium halide has an adverse effect on lithium ion conductivity, which fails to effectively inhibit the production of hydrogen sulfide.

Method used

The production of hydrogen sulfide is inhibited by introducing lithium halide with a specific structure into the solid electrolyte. The specific implementation method is to combine compound A and compound B, wherein compound A contains a crystalline phase with a sulfhydryl-silver germanium ore-type crystal structure, compound B is LiX, and its crystallite size is controlled above 25 nm to improve the conductivity of lithium ion and inhibit the production of hydrogen sulfide.

Benefits of technology

It effectively inhibits the production of hydrogen sulfide in solid electrolytes, while improving lithium ion conductivity and improving the performance of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003596295690000151
    Figure BDA0003596295690000151
Patent Text Reader

Abstract

The solid electrolyte of the present invention comprises compound A and compound B, wherein compound A comprises a crystalline phase having an argyrodite-type crystal structure and is formed by Li a PS b X c (X is at least one halogen element. a represents a number greater than 3.0 and less than 6.0. b represents a number greater than 3.5 and less than 4.8. c represents a number greater than 0.1 and less than 3.0). The compound B is represented by LiX (wherein X is the same definition as above). The crystallite size of the compound B is greater than 25 nm. The BET specific surface area of ​​the solid electrolyte is 14.0 m 2 / g or less is appropriate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte and an electrode mixture, a solid electrolyte layer and a solid-state battery using the same. Background Art

[0002] In recent years, solid electrolytes have attracted attention as an alternative to electrolyte solutions used in various liquid batteries. Solid-state batteries using such solid electrolytes are expected to be put into practical use as batteries that are safer and have higher energy density than liquid batteries using flammable organic solvents.

[0003] As a prior art related to solid electrolytes, for example, the technology described in Patent Document 1 is known. The document contains relevant records of one of the solid electrolytes used in lithium-ion batteries, namely, a sulfide solid electrolyte. As the crystal structure of the sulfide solid electrolyte, various structures are known, one of which is a argyrodite-type crystal structure. The document records that a solid electrolyte containing a compound and the compound containing a crystalline phase having a argyrodite-type crystal structure does not contain lithium halide or contains a small amount of lithium halide, which is ideal. In addition, the document also records the problem that the sulfide solid electrolyte may react with moisture in the atmosphere to produce hydrogen sulfide.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: US2019 / 305371A1 Summary of the invention

[0007] It has been previously believed that lithium halide contained in a solid electrolyte in the form of a heterogeneous phase containing a compound and the compound containing a crystalline phase having an argyrodite-type crystal structure will have an adverse effect on the lithium ion conductivity of the solid electrolyte. However, how lithium halide affects the generation of hydrogen sulfide from the solid electrolyte has not been studied so far. Therefore, the subject of the present invention is to provide a solid electrolyte that can suppress the generation of hydrogen sulfide.

[0008] The present inventors have conducted intensive research to solve the above-mentioned problems and unexpectedly found that if a lithium halide having a specific structure is present in a solid electrolyte, the generation of hydrogen sulfide from the solid electrolyte can be suppressed. The present invention is based on this finding and solves the above-mentioned problems by providing a solid electrolyte comprising a compound A and a compound B, wherein the compound A comprises a crystalline phase having an argyrodite-type crystal structure and the solid electrolyte is prepared by using Li a PS b X c(X is at least one halogen element. a represents a number greater than or equal to 3.0 and less than or equal to 6.0. b represents a number greater than or equal to 3.5 and less than or equal to 4.8. c represents a number greater than or equal to 0.1 and less than or equal to 3.0) represents,

[0009] The compound B is represented by LiX (wherein X is the same as defined above),

[0010] The crystallite size of the compound B is 25 nm or more. DETAILED DESCRIPTION

[0011] Hereinafter, the present invention will be described based on its preferred embodiments. The solid electrolyte of the present invention comprises Li a PS b X c (X is at least one halogen element. a represents a number greater than 3.0 and less than 6.0. b represents a number greater than 3.5 and less than 4.8. c represents a number greater than 0.1 and less than 3.0). Compound A is solid at room temperature (25°C) and has lithium ion conductivity. The solid electrolyte of the present invention, in addition to compound A, also includes compound B represented by LiX (wherein X has the same definition as above).

[0012] Compound A in the present invention is a crystalline material containing a crystalline phase having an argyrodite-type crystal structure. In particular, compound A may contain a glass component, i.e., an amorphous component. Compound A "containing a crystalline phase having an argyrodite-type crystal structure" means that as long as compound A contains at least a crystalline phase having an argyrodite-type crystal structure, it may also contain a crystalline phase (also referred to as "heterophase") different from the crystalline phase having an argyrodite-type crystal structure. Of course, the heterophase may not be contained. As a compound constituting the heterophase, for example, Li3PS4 can be cited.

[0013] In compound A, the ratio of the crystalline phase having an argyrodite-type crystal structure to the total crystalline phase constituting compound A may be, for example, 10% by mass or more, 20% by mass or more, or 50% by mass or more. Compound A preferably contains a crystalline phase having an argyrodite-type crystal structure as a main phase.

[0014] Here, "main phase" refers to the phase with the largest ratio relative to the total amount of all crystalline phases constituting the solid electrolyte of the present invention. Therefore, the content ratio of compound A relative to all crystalline phases constituting the solid electrolyte of the present invention is preferably 60% by mass or more, and more preferably 70% by mass or more, 80% by mass or more, or 90% by mass or more.

[0015] On the other hand, "heterogeneous phase" refers to a phase whose ratio is smaller than the above-mentioned main phase relative to the total amount of all crystalline phases constituting the solid electrolyte of the present invention. Therefore, the content ratio of compound B relative to all crystalline phases constituting the solid electrolyte of the present invention is preferably, for example, 40% by mass or less, and more preferably 30% by mass, 20% by mass or less, or 10% by mass or less.

[0016] In addition, the ratio of a crystal phase can be determined by calculating the content ratio by X-ray diffraction measurement, for example.

[0017] The crystalline phase having an argyrodite-type crystal structure refers to a crystalline phase possessed by a compound group having a mineral derived from the chemical formula Ag8GeS6. From the viewpoint of improving lithium ion conductivity, the compound A containing a crystalline phase having an argyrodite-type crystal structure particularly preferably has a cubic crystal structure.

[0018] Whether the solid electrolyte of the present invention contains a compound containing a crystalline phase having an argyrodite-type crystal structure can be confirmed, for example, by XRD measurement. That is, in an X-ray diffraction pattern measured by an X-ray diffraction device using CuKα1 rays, the crystalline phase of the argyrodite-type crystal structure has characteristic peaks at 2θ=15.34°±1.00°, 17.74°±1.00°, 25.19°±1.00°, 29.62°±1.00°, 30.97°±1.00°, 44.37°±1.00°, 47.22°±1.00°, and 51.70°±1.00°. Furthermore, for example, characteristic peaks are also present at 2θ=54.26°±1.00°, 58.35°±1.00°, 60.72°±1.00°, 61.50°±1.00°, 70.46°±1.00°, and 72.61°±1.00°. It should be noted that the "peak" in this specification refers to the apex of the peak. In addition, the aforementioned peaks preferably exist independently and do not overlap with other peaks.

[0019] In the solid electrolyte of the present invention, the crystalline phase of the argyrodite type crystal structure constituting compound A preferably forms a main phase relative to all crystalline phases. On the other hand, compound B preferably forms a subphase in the solid electrolyte of the present invention, which is a substance of a different phase from the crystalline phase of the argyrodite type crystal structure. Therefore, when an X-ray diffraction measurement is performed on the solid electrolyte of the present invention, at least a crystalline phase of the argyrodite type crystal structure and a crystalline phase derived from compound B are observed.

[0020] In the solid electrolyte of the present invention, it is preferred that the crystallite size of the compound B is controlled. This can suppress the generation of hydrogen sulfide from the solid electrolyte of the present invention. The present inventors believe that the reason is as follows.

[0021] The solid electrolyte of the present invention contains compound A as described above. If compound A is produced, compound B is sometimes inevitably present in the product. It is generally believed that compound B is a compound that has strong hygroscopicity and can absorb moisture in the air. The inventors focused on this point and further promoted the research and found that if compound B having a crystallite size larger than a specific value exists in a heterogeneous form in compound A, the hygroscopic effect of compound B becomes stronger. And, due to this, compound A is not easy to react with moisture in the air, which can inhibit the solid electrolyte of the present invention from producing hydrogen sulfide.

[0022] From the viewpoint of making the above advantageous effects more significant, in the solid electrolyte of the present invention, the crystallite size of compound B is preferably 25 nm or more, more preferably 26 nm or more, and even more preferably 27 nm or more.

[0023] In the solid electrolyte of the present invention, the lithium ion conductivity can also be improved by controlling the crystallite size of compound B. The present inventors believe that the reasons are as follows. From the viewpoint of improving the lithium ion conductivity of the solid electrolyte, it is desired that the amount of compound B present is as small as possible, and ideally, compound B is absent. However, in the current mainstream method for manufacturing compound A, it is not easy to make compound B absent in the product. Therefore, the present inventors have conducted various studies on means for improving lithium ion conductivity even when compound B coexists in the form of a heterophase in compound A containing a crystalline phase having a argyrodite-type crystal structure. As a result, it was found that by controlling the crystallite size of compound B as a heterophase to a small value, the conduction path of lithium ions in the solid electrolyte is no longer blocked, and the lithium ion conductivity of the solid electrolyte is improved.

[0024] From the viewpoint of making the above advantageous effects more significant, in the solid electrolyte of the present invention, the crystallite size of compound B is preferably 70 nm or less, more preferably less than 68 nm, and even more preferably 67 nm or less.

[0025] The crystallite size of the compound B contained in the solid electrolyte of the present invention can be determined by X-ray diffraction measurement. The specific method will be described in detail in the examples described below.

[0026] The solid electrolyte of the present invention controls the crystallite size of the compound B contained therein so that the lithium ion conductivity at room temperature (25° C.) is preferably 4.0 mS / cm or more, more preferably 4.2 mS / cm or more, and further preferably 4.5 mS / cm or more. The lithium ion conductivity of the solid electrolyte can be measured by the method described in the examples described below.

[0027] The compound B contained in the solid electrolyte of the present invention in a heterogeneous form is represented by LiX as described above. X represents at least one halogen element. Examples of X include fluorine, chlorine, bromine and iodine. When X is one, examples of compound B include LiF, LiCl, LiBr or LiI. When X is two, compound B is represented by LiX 1 y X 2 z Indicates. 1 and X 2 represents different halogen elements. In addition, y and z represent numbers that satisfy y+z=1 and are greater than 0. 1 With X 2 For example, the combination of Cl and Br (i.e., LiCl y Br z ), Cl and I, and Br and I. When X is three types, compound B is LiX 1 y X 2 z X 3 v Indicates. 1 , X 2 and X 3 represents different halogen elements. In addition, y, z, and v represent numbers that satisfy y+z+v=1 and are greater than 0. 1 With X 2 With X 3 The solid electrolyte of the present invention sometimes contains only one compound B, or sometimes contains two or more compounds B. When the solid electrolyte of the present invention contains only one compound B, the crystallite size of the compound B preferably satisfies the above range. On the other hand, when the solid electrolyte of the present invention contains two or more compounds B, it is preferred that the crystallite size of at least one compound B satisfies the above range, and it is more preferred that the crystallite sizes of all compounds B satisfy the above range.

[0028] The compound A contained in the solid electrolyte of the present invention is as described above with Li a PS b X c Here, "compound A is Li a PS b X c "Representation" means: including compound A becoming Li a PS b X cIn the composition formula, a, which represents the molar ratio of the lithium (Li) element, is preferably a number greater than 3.0 and less than 6.0, more preferably a number greater than 3.2 and less than 5.8, and further preferably a number greater than 3.4 and less than 5.4. It should be noted that a may be less than 5.4.

[0029] In the above composition formula, b representing the molar ratio of sulfur (S) element is, for example, preferably 3.5 to 4.8, more preferably 3.8 to 4.6, and even more preferably 4.0 to 4.4. It should be noted that b may be less than 4.4.

[0030] Furthermore, in the above composition formula, c is preferably a number of 0.1 or more and 3.0 or less, more preferably a number of 0.2 or more and 2.5 or less, and further preferably a number of 0.4 or more and 2.0 or less. When a, b, and c are within this range, the lithium ion conductivity of the compound A becomes sufficiently high. In the above composition formula, X represents at least one halogen element. When X is one, the compound A may include Li a PS b F c , Li a PS b Cl c , Li a PS b Br c and Li a PS b I c When X is two, compound A is Li a PS b X 1 y X 2 z Indicates. 1 and X 2 represents different halogen elements. In addition, y and z represent numbers that satisfy c=y+z and are greater than 0. 1 With X 2 For example, the combination of Cl and Br, the combination of Cl and I, and the combination of Br and I can be listed. When X is three types, compound A is Li a PS b X 1 y X 2 z X 3 v Indicates. 1 , X 2 and X 3represents different halogen elements. In addition, y, z and v represent numbers that satisfy c=y+z+v and are greater than 0. 1 With X 2 With X 3 Examples of the combination of Cl, Br and I include a combination of Cl, Br and I. The solid electrolyte of the present invention may contain only one compound A or may contain two or more compounds A.

[0031] In the present invention, the feed amount is Li a PS b X c The compound A obtained in the manner may contain elements other than lithium (Li), phosphorus (P), sulfur (S) and halogen (X). For example, part of the lithium (Li) element may be replaced by other alkali metal elements, part of the phosphorus (P) element may be replaced by other nitrogen group elements, or part of the sulfur (S) element may be replaced by other chalcogen elements.

[0032] In the present invention, it is also preferred to control the crystallite size of compound A on the basis of controlling the crystallite size of compound B. As a result, the lithium ion conductivity of the solid electrolyte of the present invention is further improved. From the viewpoint of making this beneficial effect more significant, in the solid electrolyte of the present invention, it is preferred that the crystallite size of compound A is, for example, 50 nm or more, preferably 100 nm or more, and particularly preferably 300 nm or more. On the other hand, the crystallite size of compound A can be, for example, less than 800 nm, less than 600 nm, or less than 400 nm. By making the crystallite size of compound A within the aforementioned range, the lithium ion conductivity of the solid electrolyte of the present invention can be fully improved.

[0033] When the solid electrolyte of the present invention contains only one compound A, the crystallite size of the compound A preferably satisfies the above range. On the other hand, when the solid electrolyte of the present invention contains two or more compounds A, the crystallite sizes of all the compounds A preferably satisfy the above range.

[0034] The crystallite size of the compound A contained in the solid electrolyte of the present invention can be determined by X-ray diffraction measurement. The specific method will be described in detail in the examples described below.

[0035] The solid electrolyte of the present invention may contain impurities in addition to compound A and compound B. From the viewpoint of reducing the effect on performance, the impurity content may be less than 5 mol%, preferably less than 3 mol%, and particularly preferably less than 1 mol%.

[0036] From the viewpoint of further suppressing the generation of hydrogen sulfide, the BET specific surface area of ​​the solid electrolyte of the present invention is preferably 14.0 m2 / g or less, more preferably 13.5m 2 / g or less, more preferably 13.0m 2 / g or less. From the viewpoint of suppressing the generation of hydrogen sulfide, the smaller the BET specific surface area, the better. If it is 1.5m 2 / g or more, especially 2.0m 2 / g or above, especially 2.5m 2 / g, the generation of hydrogen sulfide can be sufficiently suppressed. This range of BET specific surface area can be achieved, for example, by controlling the particle size of the solid electrolyte. The method for measuring the BET specific surface area is described in detail in the examples described below.

[0037] The solid electrolyte of the present invention comprises a powder in the form of a particle assembly. The particle size of the solid electrolyte of the present invention is the volume cumulative particle size D when the cumulative volume is 50 volume % based on the laser diffraction scattering particle size distribution measurement method. 50 It is preferably 0.7 μm or more, preferably 0.75 μm or more, and particularly preferably 0.79 μm or more. 50 For example, it is preferably 10.0 μm or less, particularly preferably 8.5 μm or less, and particularly preferably 7.0 μm or less. 50 By having the aforementioned lower limit, the generation of hydrogen sulfide from the solid electrolyte can be effectively suppressed. On this basis, the increase in the surface area of ​​the solid electrolyte powder as a whole can be suppressed, and the occurrence of undesirable conditions such as increased resistance and difficulty in mixing with the active material can be suppressed. On the other hand, by making the volume cumulative particle size D of the solid electrolyte of the present invention 50 With the aforementioned upper limit, the contact points and contact areas of the solid electrolytes are increased, and the lithium ion conductivity can be efficiently improved. On this basis, when the solid electrolyte of the present invention is used in combination with other solid electrolytes, there is also the advantage that the solid electrolyte of the present invention easily enters the gaps of the other solid electrolytes.

[0038] Due to the above D 50 The relationship between the volume cumulative particle size D when the cumulative volume of the solid electrolyte of the present invention is 10 volume % based on the laser diffraction scattering particle size distribution measurement method is 10 It is preferably 5.0 μm or less, particularly preferably 3.5 μm or less, and particularly preferably 2.0 μm or less. 10 For example, it is preferably 0.2 μm or more, particularly preferably 0.3 μm or more, and particularly preferably 0.4 μm or more.

[0039] In addition, the volume cumulative particle diameter D when the cumulative volume of the solid electrolyte of the present invention is 95 volume % based on the laser diffraction scattering particle size distribution measurement method is 95 It is preferably 40 μm or less, more preferably 30 μm or less, and particularly preferably 20 μm or less. 95 For example, it is preferably 1.5 μm or more, particularly preferably 2.0 μm or more, and particularly preferably 2.5 μm or more.

[0040] By calculating the volume cumulative particle size D 10 and D 95 Setting the content within the above range is preferred because generation of hydrogen sulfide from the solid electrolyte can be more efficiently suppressed, and contact points and contact areas between the solid electrolytes are increased, thereby more efficiently improving lithium ion conductivity.

[0041] The solid electrolyte of the present invention is suitable for manufacturing by the following method. As raw materials, a lithium source compound, a phosphorus source compound, a sulfur source compound and a halogen source compound are used. As a lithium source compound, for example, lithium sulfide (Li2S) can be used. As a phosphorus source compound, for example, phosphorus pentasulfide (P2S5) can be used. As a sulfur source compound, when the lithium source compound and / or the phosphorus source compound is a sulfide, the sulfide can be used as a sulfur source compound. As a halogen source compound, compound B (LiX) can be used. These raw materials are mixed in such a way that the lithium element, the phosphorus element, the sulfur element and the halogen element reach a specified molar ratio. In addition, by calcining the mixed raw materials in an inert atmosphere or in an atmosphere containing hydrogen sulfide gas, it is possible to obtain a Li a PS b A c The compound includes a crystalline phase having an Argentite-type crystal structure. The atmosphere containing hydrogen sulfide gas may be 100% hydrogen sulfide gas, or may be a mixed gas of hydrogen sulfide gas and an inert gas such as argon. The calcination temperature is preferably, for example, 350° C. or higher and 550° C. or lower. The holding time at the temperature is preferably, for example, 0.5 hours or higher and 20 hours or lower.

[0042] By the above method, a solid electrolyte containing compound A can be obtained. A small amount of compound B coexists in the solid electrolyte. By controlling the crystallite size of compound B, the generation of hydrogen sulfide from the solid electrolyte can be suppressed. The inventors have found that in order to suppress the crystallite size of compound B, it is beneficial to perform a predetermined pulverization process on the solid electrolyte.

[0043] The pulverization process can be carried out by wet or dry methods. In the pulverization process, various media mills can be used. As the media mill, a ball mill, a bead mill, a paint stirrer, a homogenizer, etc. can be used. As the dispersion medium used in the media mill, various ceramic balls and beads headed by aluminum oxide and zirconium oxide can be used. The diameter of the dispersion medium can be set to, for example, 0.1 mm or more and 50 mm or less.

[0044] When the pulverization treatment is performed by wet method, it is preferred to use an organic solvent as a dispersion medium from the viewpoint of being able to suppress the generation of hydrogen sulfide caused by the reaction between the solid electrolyte and water. As the organic solvent, for example, aromatic organic solvents such as toluene, xylene, benzene, and solvent naphtha; aliphatic organic solvents such as heptane, decane, n-hexane, cyclohexane, and mineral spirits can be listed. These organic solvents can be used alone or in combination of two or more.

[0045] The organic solvent is mixed with the solid electrolyte to form a slurry, and the slurry is subjected to wet grinding. From the viewpoint of smoothly obtaining a solid electrolyte with high lithium ion conductivity, the concentration of the solid electrolyte contained in the slurry is preferably set to, for example, 5 mass % or more and 50 mass % or less. In the wet grinding using a medium mill, regarding the ratio of the dispersion medium to the slurry, from the viewpoint of easily obtaining a solid electrolyte with high lithium ion conductivity, it is preferred to use a dispersion medium of 5 mass parts or more and 50 mass parts or less relative to 100 mass parts of the slurry. From the viewpoint of easily obtaining a solid electrolyte with high lithium ion conductivity, it is preferred that the dispersion time based on the medium mill is generally set to 0.5 hours or more and 60 hours or less.

[0046] When wet pulverization is performed, from the viewpoint of sufficiently increasing the crystallite size of the compound B contained in the solid electrolyte and suppressing the generation of hydrogen sulfide from the solid electrolyte, it is preferred that the volume cumulative particle size D of the solid electrolyte after wet pulverization is 0.175 mm / s. 50 The degree of pulverization is preferably adjusted to be 0.45 μm or more, more preferably 0.50 μm or more, and further preferably 0.55 μm or more. In addition, from the viewpoint of improving the lithium ion conductivity of the solid electrolyte, it is preferred that the volume cumulative particle size D of the solid electrolyte after wet pulverization is 50 The degree of pulverization is preferably adjusted to be 10 μm or less, more preferably 8.5 μm or less, and even more preferably 7.0 μm or less. From the viewpoint of controlling the crystallite size of the compound A contained in the solid electrolyte and improving the lithium ion conductivity of the solid electrolyte, it is preferred that the volume cumulative particle size D of the solid electrolyte after wet pulverization is 10 μm or less, more preferably 8.5 μm or less, and even more preferably 7.0 μm or less. 50 The degree of pulverization was adjusted so as to achieve a particle size of 10 μm or less.

[0047] The solid electrolyte of the present invention obtained in this way can be used as a material constituting a solid electrolyte layer, a material contained in an electrode mixture containing an active substance. Specifically, it can be used as a positive electrode mixture constituting a positive electrode layer containing a positive electrode active substance or a negative electrode mixture constituting a negative electrode layer containing a negative electrode active substance. Therefore, the solid electrolyte of the present invention can be used in a battery having a solid electrolyte layer, a so-called solid-state battery. More specifically, it can be used in a lithium solid-state battery. A lithium solid-state battery can be a primary battery or a secondary battery, and is preferably used in a lithium secondary battery. "Solid-state battery" means: in addition to a solid-state battery that does not contain a liquid substance or a gel-like substance as an electrolyte, it also includes, for example, a liquid substance or a gel-like substance containing less than 50% by mass, less than 30% by mass, or less than 10% by mass as an electrolyte.

[0048] The solid electrolyte layer in the solid-state battery can be manufactured by the following methods, etc.: for example, a method of dropping a slurry containing the solid electrolyte, binder and solvent of the present invention on a substrate and scraping it with a scraper or the like; a method of cutting the substrate with a scraper after contacting the slurry; a method of forming a coating film by screen printing, etc., and then removing the solvent by heating and drying. Alternatively, the powder of the solid electrolyte of the present invention can be pressed and then processed appropriately for manufacture. In addition to the solid electrolyte of the present invention, the solid electrolyte layer may also contain other solid electrolytes. The thickness of the solid electrolyte layer in the present invention is typically preferably 5 μm or more and 300 μm or less, and more preferably 10 μm or more and 100 μm or less.

[0049] From the viewpoint of improving lithium ion conductivity, the porosity of the solid electrolyte layer containing the solid electrolyte of the present invention is preferably 50% or less, more preferably 30% or less, and more preferably 20% or less. The porosity of the solid electrolyte layer can be adjusted, for example, by the pressing pressure when the solid electrolyte of the present invention in powder form is made into a powder compact. The aforementioned pressing pressure is preferably 20 MPa or more, for example.

[0050] The porosity can be calculated, for example, by the relationship shown below from the true density and apparent density of the solid electrolyte layer obtained by a liquid phase method (Archimedes method).

[0051] Void ratio (%) = (true density - apparent density) ÷ true density × 100

[0052] It should be noted that a mixture of the solid electrolyte of the present invention and other solid electrolytes can also be used as a solid electrolyte layer. When the solid electrolyte of the present invention is mixed with other solid electrolytes, the solid electrolyte of the present invention can also be used in combination with any of amorphous (glass), glass ceramics, and crystalline materials. When the other solid electrolyte mixed with the solid electrolyte of the present invention is a sulfide solid electrolyte, the sulfide solid electrolyte includes, specifically, Li2S-P2S5 system, Li4P2S6, Li7P3S 11 Etc. In addition, the solid electrolyte to be combined may be a non-sulfide, for example, an oxide-based solid electrolyte.

[0053] The solid-state battery preferably has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and the solid electrolyte layer contains the solid electrolyte of the present invention. Examples of the shape of the solid-state battery include a laminated type, a cylindrical type, and a square type.

[0054] The positive electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a positive electrode active material. As the positive electrode active material, for example, a substance used as a positive electrode active material of a lithium secondary battery can be appropriately used. As the positive electrode active material, for example, spinel-type lithium transition metal compounds, lithium metal oxides with a layered structure, etc. can be listed. In addition to the positive electrode active material, the positive electrode mixture may also contain other materials headed by a conductive auxiliary agent.

[0055] The negative electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a negative electrode active material. As the negative electrode active material, for example, a negative electrode mixture used as a negative electrode active material for a lithium secondary battery can be appropriately used. As the negative electrode active material, for example, carbon materials such as lithium metal, artificial graphite, natural graphite and difficult-graphitizable carbon (hard carbon), lithium titanate, titanium-niobium composite oxide, silicon, silicon compounds, tin and tin compounds can be listed. In addition to the negative electrode active material, the negative electrode mixture may also contain other materials headed by a conductive aid.

[0056] Example

[0057] Hereinafter, the present invention will be described in more detail by way of examples, but the scope of the present invention is not limited to these examples.

[0058] [Example 1]

[0059] To form Li 5.4 PS 4.4 Cl 0.8 Br 0.8Li2S powder, P2S5 powder, LiCl powder and LiBr powder are weighed in a manner. These powders are crushed and mixed using a ball mill to obtain a mixed powder. The mixed powder is calcined to obtain a calcined product containing lithium ion conductive sulfide. The calcination is carried out using a tubular electric furnace. During the calcination, 100% pure hydrogen sulfide gas is circulated into the electric furnace at 1.0 L / min. The calcination temperature is set to 490°C and the calcination takes 4 hours. The results of the XRD measurement confirm that the calcined product has a crystalline phase of a argyrodite-type crystal structure and LiCl 0.5 Br 0.5 of the crystalline phase.

[0060] After the calcined product is roughly crushed with a mortar and pestle, it is crushed using a hammer crusher, and the crushed product is mixed with a solvent to prepare a slurry with a concentration of 10% by mass. The slurry is supplied to a bead mill device (zirconia beads with a diameter of 0.2 mm) for wet grinding. Toluene is used as the solvent of the slurry. After wet grinding, the slurry is subjected to solid-liquid separation to dry the solid component. The dried calcined product is sieved with a sieve with a mesh of 53 μm to obtain the target solid electrolyte. In addition, other conditions such as grinding time and energy are appropriately selected according to the target solid electrolyte.

[0061] [Example 2]

[0062] The calcination temperature, pulverization device, slurry concentration and medium diameter in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0063] [Example 3]

[0064] The pulverizing device, slurry concentration and medium diameter in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0065] [Comparative Example 1]

[0066] The slurry concentration and the medium diameter in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0067] [Comparative Example 2]

[0068] The slurry concentration and the medium diameter in Example 1 were changed to the values ​​shown in the following Table 1. Except for this, the same operation as in Example 1 was carried out to obtain a solid electrolyte.

[0069] 〔Evaluation 1〕

[0070] For the solid electrolytes obtained in the examples and comparative examples, Li 5.4 PS4.4 Cl 0.8 Br 0.8 The crystallite size of the crystalline phase and LiCl 0.5 Br 0.5 In addition, the volume cumulative particle size D is measured by the following method: 10 , D 50 and D 95 , and BET specific surface area. The results are shown in Table 1 below.

[0071] 〔Determination of crystallite size〕

[0072] The measurement was performed using SmartLab manufactured by Rigaku Corporation. The optical system was set to the focusing method, a Johnson-type monochromator was used on the incident side, and a D / teX Ultra 250 was used as the detector. A Soller slit of 5 degrees was used as the parallel slit between the incident side and the light receiving side. A stand not exposed to the atmosphere was used, the scanning axis was set to 2θ / θ, the scanning range was set to 20 degrees to 140 degrees, the step width was set to 0.01 degrees, and the scanning speed was set so that the maximum peak height became 10,000 Counts or more.

[0073] Furthermore, measurement was performed under the same conditions using SRM660a (compound name: LaB6) manufactured by NIST (National Institute of Standards and Technology) as a width standard.

[0074] The analysis was performed using PDXL2 manufactured by Rigaku Corporation. The analysis steps are as follows. First, identification was performed. The CIF file (Crystallographic Information File) recorded below was read to determine the substance. The CIF file was obtained from ICSD (Inorganic Crystal Structure Database). Compound A used a file with ICSD Collection Code of 418490, and Compound B used a CIF file with ICSD Collection Code of 53818.

[0075] Next, WPPF is used to implement intensity decomposition. As a width correction, a width standard data file is selected. This file is equivalent to the file obtained by identifying the XRD data obtained by measuring SRM660a using LaB6, and analyzing and saving it using the same method as shown below. Use an external standard sample to correct the angle and width of the peak. The model function of the peak shape uses the "split Pearson VII function". Next, from the "Basic" tab, select "Intensity Decomposition" at "Precision Parameter Setting"-"Method". In addition, the lattice constant changes due to the combination of X (halogen atom) in compound B, so the initial value of the lattice constant of compound B is adjusted in a manner that the XRD data is roughly consistent with the calculated value. Next, precision is implemented. In precision, various parameters are adjusted until sufficient convergence. For example, the S value is based on 1.5 or less. The analyzed crystallite size is obtained by "Representation"-"Analysis Results".

[0076] 〔D 10 , D 50 and D 95 Determination of

[0077] The sample (powder) was placed in an organic solvent using an automatic sample feeder for a laser diffraction particle size distribution measuring device (Microtrac SDC, manufactured by Microtrac-Bell). After irradiation with 30W ultrasonic waves for 60 seconds at a flow rate of 50%, the particle size distribution was measured using a laser diffraction particle size distribution measuring device "MT3000II" manufactured by Microtrac-Bell. The volume-based particle size distribution spectrum was used to measure D. 10 , D 50 and D 95 It should be noted that toluene was used as the organic solvent.

[0078] [Measurement of BET specific surface area]

[0079] The sample (powder) was heated at 120°C for 1 hour in a vacuum using a pretreatment device "BELPREP-vacII" manufactured by Microtrac-Bell. Thereafter, the specific surface area was calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using a specific surface area measuring device "BELSORP-miniII" manufactured by Microtrac-Bell using the BET (Brunauer-Emmett-Teller) method.

[0080] 〔Evaluation 2〕

[0081] The amount of hydrogen sulfide generated by the solid electrolytes obtained in Examples and Comparative Examples was measured by the following method. The results are shown in Table 1 below.

[0082] 50 mg of each solid electrolyte was weighed in a glove box replaced with sufficiently dry Ar gas (dew point -60°C or lower), and placed in a bag sealed with a laminate film.

[0083] The dew point was adjusted to -30°C by mixing dry air with the air and the atmosphere was kept at room temperature (25°C) in a constant temperature and humidity chamber with a loading capacity of 1500cm 3 A separable flask made of glass is kept until the environment inside the separable flask reaches the same level as that inside the constant temperature and humidity chamber. Next, the sealed bag containing the solid electrolyte is opened in the constant temperature and humidity chamber, and the sample is quickly placed in the separable flask. The solid electrolyte is placed in the separable flask, and the concentration of hydrogen sulfide generated from the moment the aforementioned flask is just sealed until 60 minutes have passed is measured using a hydrogen sulfide sensor (GX-2009 manufactured by Riken Keiki Co., Ltd.) after 60 minutes. Furthermore, the volume of hydrogen sulfide is calculated from the concentration of hydrogen sulfide after 60 minutes, and the amount of hydrogen sulfide generated after 60 minutes is determined.

[0084] 〔Evaluation 3〕

[0085] The solid electrolytes obtained in Examples and Comparative Examples were measured for lithium ion conductivity by the following method. The results are shown in Table 1 below.

[0086] The solid electrolyte is uniaxially pressed in a glove box replaced with fully dry Ar gas (dew point below -60°C). Furthermore, a cold isostatic pressing device is used to form pellets with a diameter of 10 mm and a thickness of about 4 mm to 5 mm at 200 MPa. After the carbon paste as an electrode is coated on the upper and lower surfaces of the pellets, a heat treatment is performed at 180°C for 30 minutes to prepare a sample for ion conductivity measurement. The lithium ion conductivity of the sample is measured using Solartron 1255B from TOYO CORPORATION. The measurement is performed using the AC impedance method at a temperature of 25°C and a frequency of 0.1 Hz to 1 MHz.

[0087] [Table 1]

[0088]

[0089] As is clear from the results shown in Table 1, the solid electrolytes obtained in the examples have lithium ion conductivity substantially equivalent to that of the solid electrolytes of the comparative examples and can suppress the generation of hydrogen sulfide.

[0090] Industrial Applicability

[0091] According to the present invention, a solid electrolyte in which generation of hydrogen sulfide is suppressed can be provided.

Claims

1. A solid electrolyte comprising compound A and compound B, The compound A comprises a crystalline phase having an argyrodite-type crystal structure, and is treated with Li a PS b X c It indicates that, X is at least one halogen element, a represents a number of 3.0 to 6.0, b represents a number of 3.5 to 4.8, c represents a number of 0.1 to 3.0, The compound B is represented by LiX, wherein X is the same as defined above, The crystallite size of the compound B is 25 nm or more and 70 nm or less.

2. The solid electrolyte according to claim 1, wherein the BET specific surface area is 14.0 m 2 / g or less. 3 . The solid electrolyte according to claim 1 , wherein the lithium ion conductivity at 25° C. is 4.0 mS / cm or more.

4. The solid electrolyte according to claim 1 or 2, wherein The crystallite size of the compound A is greater than 50 nm.

5. The solid electrolyte according to claim 1 or 2, wherein The compound B is LiCl y Br z , where y and z are numbers satisfying y+z=1. 6 . An electrode mixture comprising the solid electrolyte according to claim 1 and an active material. 7 . A solid electrolyte layer comprising the solid electrolyte according to claim 1 . 8 . A solid-state battery comprising the solid electrolyte according to claim 1 .

Citation Information

Patent Citations

  • Sulfide solid electrolyte

    US20190305371A1

  • Sulfide-based solid electrolyte for lithium ion cell, and solid electrolyte compound

    CN107112586A